PENGARUH CAPITAL INTENSITY, PROFITABILITAS, DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK - Nadhifah, Isyfa Fuhrotun (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
Tax aggressiveness is defined as a manager's action in reducing the company's tax burden for its own sake so that it will cause tension between managers and shareholders. This happens because tax aggressiveness is carried out by managers only for short-term interests without regard to long-term benefits for the company as expected by shareholders. This study aims to examine the effect of capital intensity, profitability, and inventori intensity on corporate tax aggressiveness. The independent variables used this study are capital intensity, profitability, and inventori intensity. While the dependent variable in in this study, tax agressiveness is measured by the effective tax rate (ETR). The method of sampling is purposive sampling in accordance with research criteria, selected as many as 20 campanies with the total data obtained 60 data in 3 years. Additionally, the data analysis technique used multiple linear regression with SPSS 23. The result of this study indicate that capital intensity significantly influence the aggressiveness of corporate taxes. Profitability significantly influence the aggressiveness of corporate taxes, and inventori intensity significantly influence the aggressiveness of corporate taxes.